A retrospective cohort study of U.S. service members returning from Afghanistan and Iraq: is physical health worsening over time? - Falvo Michael J; Serrador Jorge M; McAndrew Lisa M; Chandler Helena K; Lu Shou-En; Quigley Karen S (BMC, 2012)
Abstract Background High rates of mental health disorders have been reported in veterans returning from deployment to Afghanistan (Operation Enduring Freedom: OEF) and Iraq (Operation Iraqi Freedom: OIF); however, less is known about physical health functioning and its temporal course post-deployment. Therefore, our goal is to study physical health functioning in OEF/OIF veterans after deployment. Methods We analyzed self-reported physical health functioning as physical component summary (PCS) scores on the Veterans version of the Short Form 36 health survey in 679 OEF/OIF veterans clinically evaluated at a post-deployment health clinic. Veterans were stratified into four groups based on time post-deployment: (1Yr) 0 - 365 days; (2Yr) 366 - 730 days; (3Yr) 731 - 1095 days; and (4Yr+) > 1095 days. To assess the possibility that our effect was specific to a treatment-seeking sample, we also analyzed PCS scores from a separate military community sample of 768 OEF/OIF veterans evaluated pre-deployment and up to one-year post-deployment. Results In veterans evaluated at our clinic, we observed significantly lower PCS scores as time post-deployment increased (p = 0.018) after adjusting for probable post-traumatic stress disorder (PTSD). We similarly observed in our community sample that PCS scores were lower both immediately after and one year after return from deployment (p < 0.001) relative to pre-deployment PCS. Further, PCS scores obtained 1-year post-deployment were significantly lower than scores obtained immediately post-deployment (p = 0.02). Conclusion In our clinical sample, the longer the duration between return from deployment and their visit to our clinic, the worse the Veteran's physical health even after adjusting for PTSD. Additionally, a decline is also present in a military community sample of OEF/OIF veterans. These data suggest that, as time since deployment length increases, physical health may deteriorate for some veterans.